The great impostor: Lues maligna in an HIV-infected male. (15th September 2017) - Mena Lora, Alfredo J; Braniecki, Marylee; Nasir, Ayman; Brito, Maximo
Lues maligna is a rare severe cutaneous manifestation of secondary syphilis. It is also known as malignant syphilis and ulceronodular syphilis. We report a case of a 58-year-old HIV-infected male who presented with diffuse, pruritic, non-tender, maculo-papular skin lesions, ulcerated nodules and plaques surrounded by an erythematous base. The disseminated skin lesions were at various stages and were located on his back, chest, arms and testicles. Patient had been receiving antiretroviral therapy. Laboratory studies had demonstrated CD4 lymphocyte count of 463 cells/mm 3 and an undetectable HIV viral load. Workup revealed a rapid plasma reagin of 1:256 dilutions and the skin biopsy findings were compatible with syphilis. The skin lesions resolved with intramuscular penicillin. We herein describe a rare case of lues maligna in an HIV-infected patient with a preserved immune function and viral suppression. Such skin lesions can mimic fungal or mycobacterial infections and can pose a diagnostic challenge. Even in the modern era, syphilis remains the great impostor. Clinicians must be able to recognize this condition based on clinical characteristics and risk factors to diagnose and treat this condition promptly.